Teaching potential of integrated learning technologies Smart, Stem and Steam - Aniskin, Vladimir Nikolaevich; Korostelev, Aleksandr A.; Lvovna, Busygina Alla; Kurochkin, Anatoly V.; Sobakina, Tatyana G. (Revista de la Universidad del Zulia, 2020)
At the current stage of digitization of the Russian economy, educational institutions urgently need new, more advanced and effective training technologies that help improve the quality of training of highly competent and competitive specialists who comply with the social order of society digital. These technologies should promote the introduction of robotic and cyber-physical systems in the training of future specialists. The article shows that SMART, STEM and STEAM integrated learning technologies that encompass the theoretical and practical components of educational programs with the help of special technological equipment: robotic complexes, virtual learning tools and cyber systems, can be used as technologies in the digital education. It is proven that the practical application of mathematical, physical, engineering and technological knowledge, modeling and design of robotic cybernetic devices and others, allow us to more effectively solve the tasks of the competition-oriented educational paradigm, create additional conditions for the development and realization of the personal potential of the students. The integrative didactic potential of SMART, STEM and STEAM technologies is determined, ensuring the achievement of the synergistic effect in the educational process and increasing the productivity of education subjects through the combination of the individual means of the technologies studied in a single system. The advantages of digital education are analyzed, which are optimized using the integrative teaching potential of SMART, STEM and STEAM technologies. Based on the characteristics of the integrative didactic potential of SMART, STEM and STEAM technologies, it is concluded that they are promising in the era of the digitization of Russian education and viable to use them in order to maintain the effectiveness of the educational process.